Analysis of Bare Uniform Fiber Bragg Grating Sensor for Measuring Strain on the Landing Gear of the LSU-02 Unmanned Aircraft - Anwar, Rudi Choirul; Purnamaningsih, Retno Wigajatri; Rahardjo, Sasono; Hamidah, Maratul; Martha, Aryandi; Firdaus, Muhammad Yusha; Pramudya, Tinova (Universitas Indonesia, 2024)
This paper reports the results of testing a bare uniform FBG sensor for measuring strain occurring on the landing gear of an unmanned aircraft. The landing gear used in this research is made from carbon fiber, known for its high strength and stiffness. The FBG sensor is positioned 20 cm from the center point of the landing gear, specifically at the curved section, to optimize strain detection. Static testing to measure strain was conducted by applying varying mass loads from 0 to 9 kilograms to test the sensor's response to load changes. Measurement results show a constant measurement threshold at a load of 50 grams, indicating sensor stability within that load range, with a measurement resolution of 0.1654 microstrain. Comparison of FBG measurement results with the BLFAB-55 strain gauge sensor revealed a measurement difference of 5.9%. Further research was conducted by introducing disturbances in the form of wind at speeds of 5 m/s and 10 m/s, and temperature disturbances of 30°C and 45°C. The results showed that the 45°C temperature disturbance had the most significant impact on the strain changes measured by the FBG, with an increase in strain value of 265% compared to when there was no disturbance.